2023
DOI: 10.3389/fphar.2023.1062169
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity of the medial prefrontal cortex, nucleus accumbens, and basolateral amygdala in conditioned taste aversion and conditioned place preference induced by different doses of morphine administrations in rats

Abstract: To re-examine the paradoxical effect hypothesis of abused drugs, the present study concerned whether different doses of morphine disparately affect neuronal activity and associations among the subareas of the medial prefrontal cortex (mPFC: cingulate cortex 1-Cg1, prelimbic cortex-PrL, infralimbic cortex-IL), the subregions of the nucleus accumbens (NAc; both core and shell), and the basolateral amygdala (BLA) following conditioned taste aversion (CTA) and conditioned place preference (CPP). All rats were give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Previous studies have suggested that the LiCl-induced conditioned suppression the saccharin solution intake was governed by the NAc, the anterior part of the bed nucleus of the stria terminals, and the central amygdala [ 15 ]. Moreover, the BLA and the prelimbic cortex were shown to exhibit more c-Fos expression after morphine- or amphetamine-induced conditioned suppression of the saccharin solution intake [ 36 , 37 , 38 , 39 ]. To date, no research has comprehensively examined the issue of whether the dopaminergic pathway or its subtypes of dopamine receptors from the BLA projections to the other brain areas, such as the NAc, VTA, or the subareas of the medial prefrontal cortex (i.e., the cingulate area 1, prelimbic cortex, and infralimbic cortex), actually contribute to the LiCl-induced CTA learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that the LiCl-induced conditioned suppression the saccharin solution intake was governed by the NAc, the anterior part of the bed nucleus of the stria terminals, and the central amygdala [ 15 ]. Moreover, the BLA and the prelimbic cortex were shown to exhibit more c-Fos expression after morphine- or amphetamine-induced conditioned suppression of the saccharin solution intake [ 36 , 37 , 38 , 39 ]. To date, no research has comprehensively examined the issue of whether the dopaminergic pathway or its subtypes of dopamine receptors from the BLA projections to the other brain areas, such as the NAc, VTA, or the subareas of the medial prefrontal cortex (i.e., the cingulate area 1, prelimbic cortex, and infralimbic cortex), actually contribute to the LiCl-induced CTA learning.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the present study used the emetic drug, LiCl, to induce conditioned suppression of saccharin solution intake. However, another line of behavioral studies has demonstrated that abused drugs (such as morphine [ 38 ], cocaine [ 40 ], amphetamines [ 41 ], and alcohol [ 42 ]) could also have the effect of conditioned suppression on the tastant. Until now, no research has examined whether the pathway and dopaminergic receptors of the BLA also mediate abused drug-induced conditioned suppression.…”
Section: Discussionmentioning
confidence: 99%